Teks Kitab Suci dan Mesin: Menakar Kerja Mesin Kecerdasan Buatan dalam Memfasilitasi Pemahaman Al-Qur’an - Abd. Basid; Lailatul Qomariyah; M. Fadil Asa Fatahillah Sunandar; Moh. Asasuddin (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2024)
Understanding the Koran is the most important aspect of Muslim life that requires dedication, time and in-depth knowledge. Especially in understanding the interpretation of the verses that we need. Not only textual but also contextual in understanding asbabun nuzul, the relationship between verse 1 and other verses, munasabah verses and others, what is really needed is in-depth (abstract) knowledge, not just written and systematic. In the digital era, artificial intelligence (AI) has emerged as a tool that can facilitate the understanding of the Qur'an in a revolutionary way. Thus, this research explains how artificial intelligence (AI) can provide accurate interpretation results that are in accordance with well-known interpretations. In the interpretation of the verses of the Qur'an, it is not only textual but also contextual. And how AI can provide new impetus in efforts to understand the eternal messages of the Koran. The method used in this research uses the Library Research method, which involves searching for reading sources in books, journals and libraries